Animal metaphors in Malay with semantic derogation - Md Rashid, Sabariah; Muhammad, Nurul Nadia (Universiti Putra Malaysia Press, 2013)
Zoosemy, or what is understood in the current semantic literature as the use of animal names to denote human qualities or animal metaphors, has been the subject of investigation in various languages and cultures such as English, Spanish, Hungarian and Chinese. Studies focusing on this topic have examined the role of conceptual dimension relating to APPEARANCE/PHYSICAL/CHARACTERISTIC in the process of zoosemic extension in different languages. This study examined the use of animal metaphors in Malay. Data on Malay animal metaphors were extracted from various databases, namely the electronic database on Malay peribahasa and Dewan Bahasa dan Pustaka Malay corpus. The analysis of the data focused on how domesticated animals such as cow, goat and donkey are manifested in the respective figurative expressions, i.e., what information or aspects are encoded in the source domain in the conveyance of specific meanings in the target domain of the expressions, as well as whether they have positive or negative evaluations. Findings of the analysis revealed that the behavioural characteristics, as well as the appearance of the domesticated animals, are a common source domain of animal metaphors in Malay. The general conceptual dimension of BEHAVIOUR/APPEARANCE and other specific aspects related to the domesticated Malay animals motivate the intended meaning of the expressions. The findings also illustrate that the use of domesticated animals in the Malay figurative expressions is also often negative, in that they are often employed in a derogatory sense. These findings are in line with those found in the analysis of animal metaphors in other languages, which suggest cultural universality in the conceptual mechanism of zoosemy.